对于凸函数,
∀
x
,
y
,
f
(
λ
x
+
(
1
−
λ
)
y
)
≤
λ
f
(
x
)
+
(
1
−
λ
)
f
(
y
)
\forall x,y,f(\lambda x+(1-\lambda)y)\leq \lambda f(x)+(1-\lambda)f(y)
∀x,y,f(λx+(1−λ)y)≤λf(x)+(1−λ)f(y),其中
λ
∈
[
0
,
1
]
\lambda \in [0,1]
λ∈[0,1].
对于函数
f
:
R
n
→
R
f:R^n \rightarrow R
f:Rn→R 和 函数
ϕ
:
R
→
R
\phi:R \rightarrow R
ϕ:R→R,存在
t
∈
R
,
v
∈
R
n
,
x
^
∈
R
n
t \in R,v \in R^n, \widehat{x} \in R^n
t∈R,v∈Rn,x
∈Rn,满足
ϕ
(
t
)
=
f
(
x
^
+
t
v
)
\phi(t)=f(\widehat{x}+tv)
ϕ(t)=f(x
+tv),
证明:
f
f
f 是凸函数
⟺
\iff
⟺
ϕ
\phi
ϕ 是凸函数(convex).
证:(1)
f
f
f 是凸函数
⟹
\Longrightarrow
⟹
ϕ
\phi
ϕ 是凸函数:
由于
f
f
f 是凸函数,有
f
(
λ
x
+
(
1
−
λ
)
y
)
≤
λ
f
(
x
)
+
(
1
−
λ
)
f
(
y
)
f(\lambda x+(1-\lambda)y)\leq \lambda f(x)+(1-\lambda)f(y)
f(λx+(1−λ)y)≤λf(x)+(1−λ)f(y) 对于任意的 x,y 均成立,
令
x
=
x
^
+
v
x
x=\widehat{x}+vx
x=x
+vx,
y
=
x
^
+
v
y
y=\widehat{x}+vy
y=x
+vy(任意情况都成立,部分特殊情况也肯定成立),代入上式,合并同类项,
⟹
\Longrightarrow
⟹
f
(
λ
(
x
^
+
v
x
)
+
(
1
−
λ
)
(
x
^
+
v
y
)
)
≤
λ
f
(
x
^
+
v
x
)
+
(
1
−
λ
)
f
(
x
^
+
v
y
)
f(\lambda (\widehat{x}+vx)+(1-\lambda)(\widehat{x}+vy))\leq \lambda f(\widehat{x}+vx)+(1-\lambda)f(\widehat{x}+vy)
f(λ(x
+vx)+(1−λ)(x
+vy))≤λf(x
+vx)+(1−λ)f(x
+vy)
⟹
\Longrightarrow
⟹
f
(
x
^
+
(
λ
x
+
(
1
−
λ
)
y
)
)
v
)
≤
λ
f
(
x
^
+
v
x
)
+
(
1
−
λ
)
f
(
x
^
+
v
y
)
f(\widehat{x}+(\lambda x+(1-\lambda)y))v)\leq \lambda f(\widehat{x}+vx)+(1-\lambda)f(\widehat{x}+vy)
f(x
+(λx+(1−λ)y))v)≤λf(x
+vx)+(1−λ)f(x
+vy)
由于
ϕ
(
t
)
=
f
(
x
^
+
t
v
)
\phi(t)=f(\widehat{x}+tv)
ϕ(t)=f(x
+tv),
⟹
\Longrightarrow
⟹
ϕ
(
λ
x
+
(
1
−
λ
)
y
)
≤
λ
ϕ
(
x
)
+
(
1
−
λ
)
ϕ
(
y
)
\phi(\lambda x+(1-\lambda)y)\leq \lambda \phi(x)+(1-\lambda)\phi(y)
ϕ(λx+(1−λ)y)≤λϕ(x)+(1−λ)ϕ(y)
⟹
\Longrightarrow
⟹
ϕ
\phi
ϕ 是凸函数(convex)
(2)
ϕ
\phi
ϕ 是凸函数
⟹
\Longrightarrow
⟹
f
f
f 是凸函数:
⟹
\Longrightarrow
⟹
ϕ
(
λ
x
+
(
1
−
λ
)
y
)
≤
λ
ϕ
(
x
)
+
(
1
−
λ
)
ϕ
(
y
)
\phi(\lambda x+(1-\lambda)y)\leq \lambda \phi(x)+(1-\lambda)\phi(y)
ϕ(λx+(1−λ)y)≤λϕ(x)+(1−λ)ϕ(y)
⟹
\Longrightarrow
⟹
f
(
x
^
+
(
λ
x
+
(
1
−
λ
)
y
)
)
v
)
≤
λ
f
(
x
^
+
v
x
)
+
(
1
−
λ
)
f
(
x
^
+
v
y
)
f(\widehat{x}+(\lambda x+(1-\lambda)y))v)\leq \lambda f(\widehat{x}+vx)+(1-\lambda)f(\widehat{x}+vy)
f(x
+(λx+(1−λ)y))v)≤λf(x
+vx)+(1−λ)f(x
+vy)
⟹
\Longrightarrow
⟹
f
(
λ
(
x
^
+
v
x
)
+
(
1
−
λ
)
(
x
^
+
v
y
)
)
≤
λ
f
(
x
^
+
v
x
)
+
(
1
−
λ
)
f
(
x
^
+
v
y
)
f(\lambda (\widehat{x}+vx)+(1-\lambda)(\widehat{x}+vy))\leq \lambda f(\widehat{x}+vx)+(1-\lambda)f(\widehat{x}+vy)
f(λ(x
+vx)+(1−λ)(x
+vy))≤λf(x
+vx)+(1−λ)f(x
+vy)
这里
x
^
+
v
x
\widehat{x}+vx
x
+vx 和
x
^
+
v
y
\widehat{x}+vy
x
+vy 可取到任意实数,
⟹
\Longrightarrow
⟹
f
(
λ
x
+
(
1
−
λ
)
y
)
≤
λ
f
(
x
)
+
(
1
−
λ
)
f
(
y
)
f(\lambda x+(1-\lambda)y)\leq \lambda f(x)+(1-\lambda)f(y)
f(λx+(1−λ)y)≤λf(x)+(1−λ)f(y)
⟹
\Longrightarrow
⟹
f
f
f 是凸函数
证毕。